Recent Advances in Pathophysiology, Drug Development and Future Perspectives of SARS-CoV-2 - Singh, Desh Deepak; Han, Ihn; Choi, Eun-Ha; Yadav, Dharmendra K. (Frontiers in Cell and Developmental Biology, 2020)
Abstract The coronavirus (SARS-CoV-2) pandemic is a rapidly transmitting and highly pathogenic disease. The spike protein of SARS-CoV-2 binds to the surface of angiotensin-converting enzyme-2 (ACE2) receptors along the upper respiratory tract and intestinal epithelial cells. SARS-CoV-2 patients develop acute respiratory distress, lymphocytic myocarditis, disseminated intravascular coagulation, lymphocytic infiltration, and other serious complications. A SARS-CoV-2 diagnosis is conducted using quantitative reverse-transcription PCR and computed tomography (CT) imaging. In addition, IgM or IgG antibodies are used to identify acute and convalescent illness. Recent clinical data have been generated by health workers and researchers and have shown that there is an urgent requirement in the effective clinical and treatment of patients, as well as other developments for dealing with SARS-COV-2 infection. A broad spectrum of clinical trials of different vaccines and drug treatment has been evaluated for use against SARS-COV-2. This review includes the emergence of SARS-COV-2 pneumonia as a way to recognize and eliminate any barriers that affect rapid patient care and public health management against the SARS-COV-2 epidemic based on the natural history of the disease, its transmission, pathogenesis, immune response, epidemiology, diagnosis, clinical presentation, possible treatment, drug and vaccine development, prevention, and future perspective. Keywords: Coronavirus, Pathophysiology, Epidemiology, Drug discovery, Vaccine development.